Recloser Placement on Distribution System Reliability at PT. PLN (Persero) City of Subulussalam Aceh - Faisal Irsan Pasaribu; Boonyang Plangklang; Mohd Zamri Bin Hasan (Journal of Electronics, Telecommunication, Electrical, and Physics Science, 2022)
Security of the electric power distribution system is one element of service fulfillment. The automatic return breaker or recloser is one of the 20 kV Medium Voltage Air Line safety equipment which functions to anticipate momentary disturbances so that power outages can be anticipated, the current use of electricity has expanded to almost all regions. The 20 kV distribution network often experiences disturbances both externally and internally. External disturbances are in the form of surges caused by lightning, tree branches or twigs that are exposed to the transmission line, while internal disturbances are caused by circuit breakers due to the opening and closing of circuit breakers. Interference can be temporary or permanent. Temporary interference will disappear by itself, while permanent interference requires the operator to neutralize the interference. Based on the results of the analysis of recloser placement in the distribution channel at PT. PLN (Persero) Subulussalan PK Calendar can be calculated in comparison using SAIDI, SAIFI, and FITNES. The results obtained after calculating the placement of the recloser in the front transformer position of the Koramil Sp Left with SAIDI values (0.287), and SAIFI (0.000517) and FITNES values (746268.657).